身体と食の公共性を奪うもの - 柄本 三代子 (スポーツ社会学研究, 2017)
In this paper, I discuss our encounter with a new model of agricultural practices and foods in connection with the 2020 Tokyo Olympics and Paralympics (2020 Olympics), and its significance for society. The Japanese Government has led many organizations and stakeholders to expect huge economic growth during the 2020 Olympics. We can understand this in the existing climate of neoliberalism. The agricultural sector is no exception. In this context, agricultural and foods policies connected with the 2020 Olympics are also being aggressively promoted using key terms such as “food safety” and “organic.” The organic agriculture trend has its prosperity in the 1970s, and started as a social movement to resist the economic system. The concern was directed not only to whether farmers used pesticides, but also to the resistance toward the publicness which related with body and food. Leaders of the movement aimed at the public safe construction. Consequently, that movement aimed to accomplish publicness related with food and body. However, as described above, the 2020 Olympics promotes an organic agricultural philosophy. How should we understand this phenomenon and the conditions that have given rise to it? In this paper, I discuss how the neoliberal need to deprive the publicness, has kept the relations between the 2020 Olympics and agriculture a closed subject. However, we have to think about the future. Depriving the publicness can have significant consequences for our body and food if the current global economy comes to an end. 本論は、身体や食をめぐる公共性がいかに剥奪されているかということについて考察する。そこで重要な社会的装置として機能しているのが「2020 年東京オリンピック・パラリンピック競技大会」（以下「2020 東京オリンピック」）であることを明らかにすることで、新自由主義における規範的理性がいかなるものであるか考察する。 「オーガニック」「有機農業」「GAP」「エコ」「環境保全」といった言説をともないながら親密化している「2020 東京オリンピック」と農業との結びつき方について、政府の言説を中心としてまず検討する。次に、その両者を結びつける際に重要な要素として組み込まれている有機農業の理念について検討する。有機農業とはそもそも、既存の経済システムや政策を批判してきた社会運動としての歴史を有する。そのような背景をもつ有機農業が経済成長主義かつ政府主導の「2020 東京オリンピック」といかに連動するのか。この点について考察するため、カウンターカルチャーとしての有機農業の性質についても注目する。抵抗のシンボルが商品化をへて消費者の選別につながっていく。また、近代において公共性が失われたとする議論を参照しつつ、公的領域への関心や現状に対するクリティカルなまなざしの喪失が、私たちにとってどのような意味をもつものであるか考察する。またそのベースに人的資源として価値を高める強靭な規範性もまた介在していることについて論じる。 公共性を剥奪された身体と食をめぐる規範的理性の命令は、次の二点において作用するものとしてとらえる必要がある。一点めとして、新自由主義的な枠組みで展開する「2020 東京オリンピック」と農業との経済成長に典型的な市場戦略に寄与するものとして作用する。これと同時並行的に、二点めとして、ホモ・エコノミクスみずからが人的資源としての価値を高め、あらゆる経済化競争にみずから好んで関わる方向に作用する。